Evolutionary multi-objective optimization of hybrid laminates - Beluch, Witold; Burczyński, Tadeusz; Długosz, Adam (Computer Assisted Methods in Engineering and Science; Vol 14 No 4 (2007), 2022)
The aim of the paper is to prepare an efficient method of the optimization of the hybrid fibre-reinforced laminates. Since the several optimization criteria which cannot be satisfied simultaneously are proposed, the multi-objective optimization methods have been employed. Different optimization criteria connected with the laminates' cost, the modal properties and the stiffness are considered. The multi-objective evolutionary algorithm which uses the Pareto approach has been used as the optimization method. To solve the boundary-value problem the finite element method commercial software has been employed. Numerical examples presenting the effectiveness of the proposed method are attached.